The Biopolitics of Asylum Law in Texas: The Case of Mexicans Fleeing Drug Violence in Juárez. - Ariadna Estévez (Norteamérica)
Using Michel Foucault’s concept of biopower, this article examines the role of asylum law in the control of Mexican migration to the U.S., arguing that U.S. authorities are using asylum law as a new means of regulating Mexican immigration. The article relies on theoretical input and empirical data to prove that there are extra-legal and technical legal issues allowing for the biopolitical use of asylum law, usually linked to sovereign power.